2008
DOI: 10.1080/02671520802048752
|View full text |Cite
|
Sign up to set email alerts
|

Musical genre and gender as factors in higher education learning in music

Abstract: Educational and psychological research suggests that gender and musical genre can influence musical learning and the development of musical identities, particularly during adolescence. However, there is a relative paucity of educational studies in higher education (HE) concerning the possible impact on musical learning of gender and musical genre, either individually or collectively. As part of a two-year comparative study funded under the Economic and Social Research Council (ESRC)'s Teaching and Learning Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 25 publications
(24 reference statements)
4
36
0
2
Order By: Relevance
“…Sandgren, 2009;Welch et al, 2008). Welch et al even claim that, "the requirements for highly skilled musical performance can transcend particular group characteristics" (p. 203).…”
Section: Discussion and Educational Implicationsmentioning
confidence: 94%
“…Sandgren, 2009;Welch et al, 2008). Welch et al even claim that, "the requirements for highly skilled musical performance can transcend particular group characteristics" (p. 203).…”
Section: Discussion and Educational Implicationsmentioning
confidence: 94%
“…All musicians, irrespective of genre, have a very strong musical identity, with their ‘musician self’ forming a core component of their overall sense of identity ( cf. Welch et al , 2008). Nevertheless, each of the groups of participants in our research, whether undergraduate music students, post‐graduate intending music teachers or newly qualified teachers, recognised that the teaching of music requires more than musical knowledge and skills, of being an excellent musician.…”
Section: Resultsmentioning
confidence: 99%
“…My own research suggests that this is too simplistic. Second, empirical research into a range of cognitive and social psychological constructs with music students lends limited support to the notion that students who specialise in different musical genres are significantly different on these constructs (Welch, et al, 2008), though the same team have identified some significant differences in terms of what is valued in a performance (Creech, et al, 2008). It has not been my argument in this paper that students are Ôsingle styleÕ musicians, nor that specialising in a particular musical style gives rise to a defined set of distinctive psychological characteristics (though see Rentfrow & Gosling, 2003).…”
Section: Resultsmentioning
confidence: 99%